If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2t + 6) = -96 Reorder the terms: -8(6 + 2t) = -96 (6 * -8 + 2t * -8) = -96 (-48 + -16t) = -96 Solving -48 + -16t = -96 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -16t = -96 + 48 Combine like terms: -48 + 48 = 0 0 + -16t = -96 + 48 -16t = -96 + 48 Combine like terms: -96 + 48 = -48 -16t = -48 Divide each side by '-16'. t = 3 Simplifying t = 3
| 4(f-3)=0 | | sin(2x)-cos(x)-2sin(x)-1=0 | | -10(s+2)=14 | | 7(4x-1)-2(5x+6)=2x-11 | | 20.28+32x^2-50.96x=0 | | 4(a-3)=36 | | 8x-vw=y-w | | 3(8)+5y=52 | | 50+50*0+1= | | 3a^2-21a=0 | | 9(4x-5)=12x-4(x-6) | | 34x-14= | | -2sin^2x+sinx-1=0 | | 1.2n^3-15n^2+100n=14986 | | 4+3+6-10= | | Log(x)9=2 | | 2-2+3-2= | | 200x^2-80x-384=0 | | 0.04(2500)+0.06(2500)=120 | | 2cos*2x-3=2 | | x^2+x^3=100 | | y^2+8y-384=0 | | 9x+4y=3x+8 | | 6x-12y+15u=0 | | 3+-3*6+-2=0 | | 5a-6=4a+5 | | 0.04x+0.06y=2500 | | 10-3(4a-3)=2(3a-4)-9 | | 25x+50x=10000 | | abx=3abx+xb^2+xa^2+bx^2+ax^2+a^2b+b^2a | | x^3-68x-308=0 | | x^2+521x+223=0 |